2017
DOI: 10.4054/demres.2017.36.60
|View full text |Cite
|
Sign up to set email alerts
|

Fertility among descendants of immigrants in Belgium: The role of the partner

Abstract: BACKGROUNDResearch on the fertility behavior of descendants of immigrants has focused on female characteristics and has largely neglected those of the male partner. One key aspect is whether the partner is of same (endogamous) or of different (exogamous) ethnic origin. Moreover, the male partner may be born in the same country as the female partner, or he may have migrated to that country later in the life course. Consequently, both his ethnic origin and migration history may affect the fertility behavior of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
1
14
0
1
Order By: Relevance
“…Ford 1990;Andersson 2004). Secondly, significantly reduced hazard ratios for women of African and Middle Eastern origin who have partnered with native Finns corroborates earlier studies concerning the role of the partner in the adaptive process (Andersson and Scott 2007;Scott and Stanfors 2011;van Landschoot et al 2017). On the other hand, however, differences of the patterns from those of the host population for characteristics such as educational attainment shows that fertility adaptation is still far from complete in our study population.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Ford 1990;Andersson 2004). Secondly, significantly reduced hazard ratios for women of African and Middle Eastern origin who have partnered with native Finns corroborates earlier studies concerning the role of the partner in the adaptive process (Andersson and Scott 2007;Scott and Stanfors 2011;van Landschoot et al 2017). On the other hand, however, differences of the patterns from those of the host population for characteristics such as educational attainment shows that fertility adaptation is still far from complete in our study population.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…For the descendants of immigrants, research has demonstrated the salience of the main language spoken in the parental home (Pailhé 2017). Furthermore, partnering with host country natives appears to play an important role in facilitating the faster adaptation of migrants' and their descendants' childbearing behaviour (Saenz et al 1994;Andersson and Scott 2007;Scott and Stanfors 2011;Stichnoth and Yeter 2013;van Landschoot et al 2017).…”
Section: Theoretical Perspectives and Previous Findingsmentioning
confidence: 99%
“…The family migrants’ fertility may have declined due to changed background of the child’s father . Research from Norway and elsewhere shows that people with immigrant background often have higher fertility if their partner is also an immigrant (Mohn 2016 ; Van Landschoot et al 2017 ), and immigrant women who prefer a Norwegian partner may also have fertility preferences closer to the Norwegian level. However, the share of births among all newly arrived immigrant women where the father was Norwegian, decreased rather than increased after 2000.…”
Section: Resultsmentioning
confidence: 99%
“…Some groups (e.g., UK-born Pakistanis and Bangladeshis in the United Kingdom) continue to marry someone from overseas and hence migration remains associated with marriage (see Berrington 2018). Moreover, the ethnicity of the partner (endogamy versus a mixed marriage) may be crucial for fertility behaviour (Milewski 2010b, van Landschoot et al 2017. Here, the question to be asked relates to the role of causality between marriage type and fertility and the selection into a mixed marriage.…”
Section: Descendants Of Immigrants: Acculturation Vs Subculture and mentioning
confidence: 99%